eCM 2012
DOI: 10.22203/ecm.v024a30
|View full text |Cite
|
Sign up to set email alerts
|

Fighting for territories: time-lapse analysis of dental pulp and dental follicle stem cells in co-culture reveals specific migratory capabilities

Abstract: Stem cell migration is a critical step during the repair of damaged tissues. In order to achieve appropriate cell-based therapies for tooth and periodontal ligament repair it is necessary first to understand the dynamics of tissue-specific stem cell populations such as dental pulp stem cells (DPSC) and dental follicle stem cells (DFSC). Using time-lapse imaging, we analysed migratory and proliferative capabilities of these two human stem cell lines in vitro. When cultured alone, both DPSC and DFSC exhibited lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…As well as in a study by Schiraldi et al (2012), [36] on the migratory capacity of stem cells from pulp and dental follicle, we also observed that stem cells from the dental follicle followed a circular motion and explored the local environment. Huang et al (2006) [37] found that 1 to 2 weeks after the beginning of culture, the cell colonies contained fibroblast-like shape, and this shape was retained after 5 or more passageways.…”
Section: Discussionsupporting
confidence: 81%
“…As well as in a study by Schiraldi et al (2012), [36] on the migratory capacity of stem cells from pulp and dental follicle, we also observed that stem cells from the dental follicle followed a circular motion and explored the local environment. Huang et al (2006) [37] found that 1 to 2 weeks after the beginning of culture, the cell colonies contained fibroblast-like shape, and this shape was retained after 5 or more passageways.…”
Section: Discussionsupporting
confidence: 81%
“…The final melting curve was performed from 55°C to 95°C. Samples were run in triplicates and the expression of specific mRNA relative to the control was determined after normalization with respect to HPRT housekeeping gene (internal control) [25]. The fold-change of mRNA expression of the genes under evaluation was calculated by using the 2 −∆∆ Ct comparative threshold method (∆Ct = difference of ∆Ct between treated cells and non-treated cells used as controls).…”
Section: Qrt-pcr Analyses Of Adipogenic Markersmentioning
confidence: 99%
“…This chemokine is associated with neuroinflammatory responses and could be involved in guiding neural progenitors to sites of brain damage (Tran et al, 2007). Growing number of studies indicates that MSCs home to sites of injury in response to cytokines and chemokines through the expression of their receptors (Schiraldi et al, 2012). CXC chemokine ligand 10 (CXCL10/IP-10) chemoattracts CXCR3-positive cells during pulpal immune response (Adachi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%